The Correlation between Listening Strategy and Students’ Listening Achievement - Anggraeni, Meri; Sugiarto, Dody; Rasuan, Zulfikri Betyar (English Education Department, 2023)
The purpose of this study was to determine the relationship between students' listening achievement and their listening approach. The participants in this study were 11th graders. 97 students served as the study's sample population. The data were analyzed using Pearson's r correlation coefficients in this descriptive quantitative study. Data were gathered for this study using a listening test and a questionnaire. Students' listening techniques were discovered using a questionnaire, and their listening abilities were discovered through a listening exam. 28 questions about cognitive, metacognitive, and socio-affective strategies were included in the questionnaire that the students were required to complete. According to the study's findings, there is a high association between the use of cognitive methods and successful listening. The link between socio-affective variables and listening achievement was significant with moderate interpretation, as was the correlation between metacognitive approach and listening achievement. Students' listening strategies and listening achievement at the school exhibit a substantial association, with rxy of cognitive strategy showing > = 0.622, metacognitive strategy showing > = 0.525, and socio-affective strategy showing > = 0.415. As a result, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is disproved.